A parametric study of broadband planar inverted F antenna (PIFA) for WLAN application - Azremi, Abdullah Al Hadi; Saidatul Norlyana, Azemi; R. Badlishah, Ahmad; Soh, Ping Jack (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org